Expected Roles and Functions of the School Management Committee: An Investigation for Effective Functioning - Sehrawat, Meena; Roy, M. M. (South Asian Journal of Social Sciences and Humanities, 2021)
Community has always been essential in giving significant education to children and members of  a community have taken the liability of educating their children. Attempts have been made to  improve participation of the community in schools by creating committees like Village Education  Committees and School Management Committees. But questions always remain, how far are the  communities practically engaged with schools? Significant provisions concerning constitution and  functions of SMCs are given in sections of the RTE Act, 2009. With the above in background the  present study was taken up with two broad objectives: first, to study the expected roles and  functions of the school management committee; and, second to find out and suggest measures for  smooth functioning of school management committee. A descriptive survey method was used to  collect the data from 390 school management committee members using Questionnaire. The data  were quantitatively analyzed using percentage. Responses obtained through questionnaire were  converted in to frequencies followed by their conversion in to percentage. Findings revealed that  members involved themselves in the monitoring of the admission, attendance and participation of  child but didn’t ensure some of the key expected roles and functions and in order to function  smoothly, SMCs should be elected through proper election process as per RTE act and SMC  members should be oriented by the principals and other authorities. This study can be useful for  all the stakeholders involved at the planning, implementing and evaluating the functioning of the  School management Committee or community participation in schools. This study focusses on  expected roles and functions of school management committee as per the RTE Act and finds new  that if members do not function as per the RTE Act, municipal school which is the miniature of  the society is going to suffer in providing the quality education as well as implementation of true  decentralization.
Keywords: Community Participation; Mid- day Meal; Right to Education Act; Roles and Functions; School Based Management; School Development Plan; School Management Committee